Differences in visual information-seeking behavior between expert and novice time-trial cyclists - Boya, M.; Foulsham, T.; Hettinga, F.; Parry, D.; Williams, E. L.; Jones, H. S.; Sparks, S. A.; Marchant, D.; Ellison, P.; Bridge, C.; Midgley, A.; McNaughton, L.; et al. (Journal of Science and Cycling, 2015)
Introduction: Pacing can be defined as an ability to distribute available energy resources during the race (Hettinga et al., 2006). It`s a determinant of athletic performance, affected by an interaction between previous experience, performance feedback and individual risk-traits (Micklewright et al., 2014). Selective processing of internal physiological and external feedback information is a complex process that informs pace decision-making (Renfree et al., 2014), but little is known about how athletes seek-out and interpret information to make pacing decisions. This study compared information-seeking behavior between novice and experienced cyclists.